Implementasi Pembelajaran PKN Berbasis Teknologi Informasi dan Komunikasi di Era Digital - Anastasia Desmeria Br Ginting; Imel Fitaloca Tambunan; Kornelia Efifani Br Tarigan; Sofia Maharaja; Sufina Khairani; Waliyul Maulana Siregar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to describe the implementation of Civic Education (Pendidikan Kewarganegaraan/PKn) learning based on Information and Communication Technology (ICT) in the digital era. PKn learning integrated with ICT is expected to improve the quality of learning to be more interactive, engaging, and relevant for students. This research outlines the important role of civic education in shaping the character and national awareness of the younger generation. The integration of ICT in PKn learning is expected to provide a more dynamic and in-depth learning experience for students through wider access to learning resources, more active interaction between teachers and students, and more engaging delivery of materials through various media.